A Flexible Bilayer Actuator Based on Liquid Crystal Network and PVDF–TrFE for Low‐Grade Waste Heat Harvesting. Issue 10 (8th September 2020) - Han, Ying; Jiang, Chunli; Fu, Hanmei; Luo, Chunhua; Lin, Hechun; Peng, Hui
Abstract : Flexible low‐grade waste heat generators are a promising device that can both recycle thermal energy and exhibit elasticity, are light weight, and have easily customized shapes. However, most thermal energy recovery technologies only work at large temperature gradients. Herein, a dynamic generator based on liquid crystal network (LCN) and poly(vinylidenedifluoride–trifluoroethylene) (PVDF–TrFE) is reported. The generator can operate in a temperature of ≈30 °C with a temperature difference of 6 K. LCN expands and shrinks in the temperature fluctuation, which is beneficial for PVDF–TrFE exposure to greater temperature changes. The device is found to exhibit a maximum output voltage of ≈4.5 mV based on pyroelectric and piezoelectric effect. This simple strategy may broaden applications of liquid crystalline actuators for harvesting low‐grade waste heat. Abstract : A dynamic generator based on liquid crystal networks (LCN) and poly(vinylidenedifluoride–trifluoroethylene) (PVDF–TrFE) is reported to convert low‐grade heat into electricity by film self‐oscillation. The generator can operate with a temperature difference of 6 K. The device is found to exhibit a maximum output voltage of ≈4.5 mV based on pyroelectric and piezoelectric effects.